Investigating the Relationship between Childhood Trauma and Hyper-Independence among University Students: From Adversity to Self-Reliance - Dr. Leenah Askaree; Kanza Safdar; Juwairiah Fraooqui; Hurmat Umar; Rubab Jan Panhwar; Lareb Kareem Baloch (Research Journal of Psychology, 2025)
Childhood trauma has been identified as a significant factor influencing psychological and behavioral outcomes in adulthood. This study investigates the relationship between childhood trauma and hyper-independence among university students, focusing on how adverse experiences shape self-reliance. Hyper-independence, often characterized as an excessive need for autonomy, is hypothesized to emerge as a coping mechanism in response to early-life adversities (Tanasugarn, 2025). The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews, to explore the prevalence and psychological underpinnings of hyper-independence in a sample of 200 university students. Findings indicate that students with a history of childhood trauma, including emotional neglect and parentification, exhibit higher levels of hyper-independence compared to their peers (Bahar, 2023). These results suggest that hyper-independence may serve as both a protective strategy and a potential barrier to forming healthy interpersonal relationships. Implications for mental health interventions and support systems in academic settings are discussed, emphasizing the need for trauma-informed care to address the unique challenges faced by hyper-independent individuals (Perry & Szalavitz, 2017).